2016
DOI: 10.1063/1.4951710
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension of ab initio liquid water at the water-air interface

Abstract: ABSTRACT:We report calculations of the surface tension of the water-air interface using ab initio molecular dynamics (AIMD) simulations. We investigate the simulation cell size dependence of the surface tension of water from force field molecular dynamics (MD) simulations, which show that the calculated surface tension increases with increasing simulation cell size, thereby illustrating that a correction for finite size effects is required for the small system used in the AIMD simulation. 2The AIMD simulations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 100 publications
5
61
0
Order By: Relevance
“…For numerical reasons, the intermolecular pair potential in molecular simulation needs to be truncated. However, thermodynamic properties in heterogeneous systems are very sensitive to a truncation of the intermolecular potential [10,11,38,[47][48][49][50][51][52][53][54][55][56]. For the Lennard-Jones potential, a large variety of long-range corrections (LRC) exist for heterogeneous systems to account for the inhomogeneity, ranging from Ewald summation techniques [57][58][59], the Fast Multipole Method (FMM) [60] and Multilevel Summation (MLS) [61] to slab-based LRC techniques [62][63][64].…”
Section: Simulations With the Mie Potentialmentioning
confidence: 99%
“…For numerical reasons, the intermolecular pair potential in molecular simulation needs to be truncated. However, thermodynamic properties in heterogeneous systems are very sensitive to a truncation of the intermolecular potential [10,11,38,[47][48][49][50][51][52][53][54][55][56]. For the Lennard-Jones potential, a large variety of long-range corrections (LRC) exist for heterogeneous systems to account for the inhomogeneity, ranging from Ewald summation techniques [57][58][59], the Fast Multipole Method (FMM) [60] and Multilevel Summation (MLS) [61] to slab-based LRC techniques [62][63][64].…”
Section: Simulations With the Mie Potentialmentioning
confidence: 99%
“…For the more accurate water models, such as polarizable models, even the simple task of structurally relaxing supercooled water can be prohibitively costly. For instance, the timescales accessible to state-ofthe-art ab initio MD simulations do not typically exceed 100 ps [117], which is considerably shorter than the characteristic structural relaxation time of supercooled water computed from typical classical non-polarizable forcefields [118]. This is in addition to the activated nature of ice nucleation, which usually involves crossing large nucleation barriers that can, sometimes, be only overcome by employing advanced sampling techniques.…”
Section: Study Of Homogeneous Ice Nucleationmentioning
confidence: 99%
“…36 The choice of BLYP exchange and correlation functionals plus D3 correction arises from the fact that this combination can reproduce both the surface tension 37 and SFG spectra 38 accurately. Furthermore, the absorption energy calculation of water on rutile TiO 2 surface demonstrated that the van der Waals corrections are essential for reproducing the water conformation (molecular vs dissociated state) on the TiO 2 surface.…”
mentioning
confidence: 99%